Oil removal material as well as preparation method and application thereof
By using precursors such as tetraethyl orthosilicate, ferrous acetate, magnesium acetate and other precursors in the coal chemical industry for hydrothermal modification in the high pressure reactor, oil removal materials with high specific surface area and high adsorption capacity were prepared, which solved the problems of low oil removal rate and unstable material in the prior art, and achieved the effects of efficient, deep oil removal and multiple regeneration cycles.
Patent Information
- Application Number
- CN202510368924.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The prior art When recovering ammonia water in the coal chemical industry, the oil removal rate is low, making it difficult to meet the deep oil removal requirements under high pH conditions. In addition, impurities may be introduced in the material during adsorption process, affecting the quality of ammonia water.
Tetraethyl orthosilicate, ferrous acetate, and magnesium acetate are used as precursors to carry out hydrolysis and condensation reactions in solvent and hydrochloric acid medium systems, followed by hydrothermal modification in an autoclave, and finally, through calcination molding, an oil removal material with a high specific surface area and high adsorption capacity is prepared.
The material exhibits efficient oil removal performance under high pH conditions, the oil content can be reduced to below 2ppm, and is chemically stable, does not react with ammonia water, avoiding secondary pollution to ammonia water during oil removal, and is suitable for multiple regeneration and recycling.
Smart Images

Figure CN119869441A_ABST
Abstract
Description
Technical Field
[0001] The embodiment of the present invention relates to the technical field of coal chemical industry recovery of ammonia water deoiling, and specifically to an oil removal material and a preparation method and application thereof. Background Art
[0002] In the coal chemical industry, the recovery of ammonia water is of great significance, because ammonia water is not only a valuable chemical, but also pollutes the environment if not properly handled. Commonly used ammonia water recovery technologies include ammonia stripping, distillation, absorption, membrane separation, ion exchange, etc. The ammonia water produced in the coal chemical process usually comes from the gasification of coal, the production of synthetic ammonia, and the processing of other by-products. Some oil substances may be mixed in these processes, resulting in the color and slag volume of ammonia water failing to meet the recovery standards, significantly affecting the quality of the recovered ammonia water. If ammonia water cannot be effectively reused, it will not only cause a waste of resources, but also increase the cost of hazardous waste treatment at the back end. At present, the main oil removal materials on the market, such as resins, are mostly used for oil removal under acidic conditions. The adsorption capacity will be significantly reduced under alkaline conditions. The development of oil removal adsorption materials suitable for high pH conditions of ammonia medium systems has important application value.
[0003] Patent CN117244515A published "Oil removal material for treating residual ammonia water from coking, and its preparation and use method", uses sulfur and edible oil to directly react to prepare sulfide, and further stirs it with coke powder and asphalt at 140-180°C. The material has the characteristics of high surface area and low specific gravity, has affinity for tar in residual ammonia water from coking, meets the factory's use requirements for treating residual ammonia water from coking, and can be regenerated and reused. However, the oil removal rate of this material generally does not exceed 80%, and the deep oil removal effect on ammonia water is still limited.
[0004] Patent CN109364895B "A method for preparing a carboxylated ferroferric oxide-polyamidine composite oil removal material" discloses a method for preparing a carboxylated ferroferric oxide-polyamidine composite oil removal material. The material is a composite material of carboxylated ferroferric oxide-polyamidine, which is mainly self-assembled by electrostatic attraction and hydrogen bonds with the large amount of positive charge carried by polyamidine and carboxylated ferroferric oxide, and has a good adsorption effect on negatively charged petroleum particles in petroleum wastewater, and can achieve the purpose of rapid oil-water separation through an external magnetic field. Since the adsorption and oil removal process utilizes electrostatic adsorption, the material is only suitable for negatively charged petroleum particles, and the removal range of oil-containing substances will be limited.
[0005] Patent CN112047550A discloses a system and method for treating wastewater containing complex organic pollutants and ammonia nitrogen, which uses an adsorption reaction and high-efficiency separation unit, a phenol recovery unit and an ammonia recovery unit connected in sequence to remove oil and suspended solids in wastewater. The deoiling powder adsorbent used is powdered activated carbon or diatomaceous earth with a particle size of 100-300 mesh, and resin is used at the rear end to deeply remove phenolic substances therein. However, since the adsorption of oil by the powdered activated carbon or diatomaceous earth used is not specific, it may cause a decrease in the concentration of ammonia water, resulting in the loss of ammonia water, and the depth of adsorption and deoiling by such adsorbents is limited. Summary of the invention
[0006] To this end, the embodiment of the present invention provides an oil removal material and its preparation method and application. The material uses tetraethyl orthosilicate, ferrous acetate, and magnesium acetate as precursors, and undergoes hydrolysis and condensation reactions in a solvent and hydrochloric acid (as a catalyst) medium system, and then undergoes hydrothermal modification in a high-pressure reactor under the action of hexadecyltrimethylammonium chloride (as a template agent), and finally undergoes calcination and molding. The material has good thermal stability, large specific surface area, high adsorption capacity, and can be regenerated and recycled for multiple times. It is particularly suitable for oil removal and purification of recovered ammonia water in the coal chemical industry, and has potential industrial application prospects.
[0007] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:
[0008] According to a first aspect of an embodiment of the present invention, the present invention provides a method for preparing an oil removal material, the method comprising the following steps:
[0009] (1) tetraethyl orthosilicate, ferric acetate and magnesium acetate are subjected to hydrolysis and condensation reaction in the presence of a solvent and hydrochloric acid to form a transparent sol, and the sol is subjected to vacuum freeze-drying and grinding to obtain a powder;
[0010] (2) the powder is subjected to a hydrothermal reaction with water and hexadecyltrimethylammonium chloride in a high-pressure reactor to obtain a hydrothermal product;
[0011] (3) The hydrothermal product is centrifuged and washed, and then calcined at 500-600° C. to obtain the degreasing material.
[0012] Furthermore, in step (1), the molar ratio of tetraethyl orthosilicate, ferrous acetate and magnesium acetate is 10:1-2:0.5-1;
[0013] The solvent is ethanol, and the volume ratio of the solvent to tetraethyl orthosilicate is 20-100:1;
[0014] The concentration of the hydrochloric acid is 0.5-3 mol / L, and the volume ratio of the hydrochloric acid to the solvent is 1:15-30;
[0015] The temperature of the hydrolysis and condensation reaction is 10-50°C and the time is 1-3h;
[0016] The vacuum freeze drying conditions are: temperature -30°C to -20°C, vacuum degree 5 to 10Pa, and time 12 to 24h;
[0017] The particle size of the powder is 30-150 μm.
[0018] Furthermore, in step (2), the solid-liquid ratio of the powder to water is 1-4:10, and the solid-liquid ratio of hexadecyltrimethylammonium chloride to water is 2-5:100;
[0019] The temperature of the hydrothermal reaction is 180-220° C. and the time is 2-4 hours.
[0020] Furthermore, in step (3), the solvent used for washing is deionized water and ethanol;
[0021] The calcination time is 2 to 5 hours.
[0022] According to a second aspect of the embodiments of the present invention, the present invention provides an oil removal material, which is made by any of the methods described above.
[0023] According to a third aspect of an embodiment of the present invention, the present invention provides the use of the above-mentioned oil removal material in the oil removal treatment of ammonia water recovery in the coal chemical industry.
[0024] According to a fourth aspect of an embodiment of the present invention, the present invention provides an oil removal method for recovering ammonia water in a coal chemical industry, the method comprising:
[0025] The oil-containing ammonia water and the oil removal material as described above enter the oil removal reaction unit for adsorption reaction to obtain a mixed liquid;
[0026] The mixed liquid enters the solid-liquid separation unit for solid-liquid separation to obtain the oil-absorbed material and the oil-removed ammonia water;
[0027] The oil-absorbed material enters the regeneration unit to undergo a desorption reaction with the regeneration liquid, and the resulting regenerated material returns to the oil removal reaction unit for reuse.
[0028] Furthermore, the mass ratio of the oil content in the oil-containing ammonia water to the oil removal material is 1:10-50, and the hydraulic retention time of the oil removal reaction unit is 1-3 hours.
[0029] Furthermore, the solid-liquid separation includes centrifugal separation or ceramic membrane filtration, wherein the rotation speed of the centrifugal separation is 1000~3000 rpm / min, and the pore size of the ceramic membrane is 0.5~5 μm.
[0030] Furthermore, the solid-to-liquid ratio of the oil-absorbed material to the regeneration liquid is 1:5-20;
[0031] The regeneration liquid is ethanol with a volume fraction of more than 98%, and the temperature of the desorption reaction is 20-40°C; or, the regeneration liquid is a sodium hydroxide aqueous solution with a mass fraction of 3%-5%, and the temperature of the desorption reaction is 60-80°C.
[0032] The embodiments of the present invention have the following advantages:
[0033] (1) The material provided by the present invention has a high specific surface area, which can reach 32~45 m 2 / g, in the adsorption and oil removal reaction, it can provide more active sites for adsorption reaction, and the adsorption capacity is greater than 20 mg / g (oil / material).
[0034] (2) The material provided by the present invention can effectively remove oil from ammonia water under high pH conditions, and the oil content in ammonia water can be reduced to below 2 ppm, thereby overcoming the disadvantage that general oil removal materials are only suitable for oil removal under low pH conditions.
[0035] (3) The material provided by the present invention has good chemical stability, does not react with ammonia water, does not introduce impurities during the adsorption process, and does not cause a decrease in the concentration of ammonia water. It is a specific adsorption and oil removal process, avoiding the problem of secondary contamination of ammonia water during the oil removal process.
[0036] (4) The material provided by the present invention can be regenerated using ethanol or hot sodium hydroxide solution, can be used multiple times, has low cost, and is suitable for engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0038] Figure 1 The present invention provides a flow chart of the oil removal process for recovering ammonia water in the coal chemical industry. DETAILED DESCRIPTION
[0039] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] This embodiment provides an oil removal material, and the preparation method thereof comprises the following steps:
[0042] (1) Add 10 ml of tetraethyl orthosilicate, 0.86 g of ferric acetate, and 0.64 g of magnesium acetate (the molar ratio of Si, Fe, and Mg is 10:1:1) to 1 L of ethanol, then slowly add 50 ml of 1 mol / L hydrochloric acid, and stir at 40 °C for 2 h. Transfer the formed transparent sol to a vacuum freeze dryer, dry at -20 °C, 5 Pa for 24 h, and grind thoroughly to obtain a powder with a particle size of 30-150 μm.
[0043] (2) 30 g of the powder obtained in step (1) was transferred to a high-pressure reactor with an effective volume of 200 ml, 150 ml of water was added for mixing, and then 4.5 g of hexadecyltrimethylammonium chloride (CTAC) was added. The reactor was reacted at 200° C. for 2 h and then naturally cooled.
[0044] (3) The product after the hydrothermal reaction was separated by centrifugation, washed three times with deionized water and ethanol, each time with 100 ml, and then calcined in a muffle furnace at 550° C. for 4 hours to obtain an oil-removing material.
[0045] Example 2
[0046] This embodiment provides an oil removal material, and the preparation method thereof comprises the following steps:
[0047] (1) Add 10 ml of tetraethyl orthosilicate, 0.86 g of ferric acetate, and 0.32 g of magnesium acetate (Si, Fe, Mg molar ratio of 10:1:0.5) to 1 L of ethanol. Then slowly add 65 ml of 1.5 mol / L hydrochloric acid, stir thoroughly at 40°C for 3 h, transfer the formed transparent sol to a vacuum freeze dryer, dry at -20°C, 5 Pa for 24 h, and grind thoroughly to obtain a powder with a particle size of 30-150 μm.
[0048] (2) 30 g of the powder obtained in step (1) was transferred to a high-pressure reactor with an effective volume of 200 ml, 150 ml of water was added for mixing, and then 3.2 g of hexadecyltrimethylammonium chloride (CTAC) was added. The reactor was reacted at 220° C. for 2 h and then naturally cooled.
[0049] (3) The product after the hydrothermal reaction was separated by centrifugation, washed three times with deionized water and ethanol, each time with 100 ml, and then calcined in a muffle furnace at 550° C. for 4 hours to obtain an oil-removing material.
[0050] Example 3
[0051] This embodiment provides an oil removal material, and the preparation method thereof comprises the following steps:
[0052] (1) Add 10 ml of tetraethyl orthosilicate, 1.29 g of ferric acetate, and 0.32 g of magnesium acetate (Si, Ca, Mg molar ratio of 10:1.5:0.5) to 1 L of ethanol. Then slowly add 50 ml of 1 mol / L hydrochloric acid, stir thoroughly at 40°C for 2 h, transfer the formed transparent sol to a vacuum freeze dryer, dry at -20°C, 5 Pa for 24 h, and grind thoroughly to obtain a powder with a particle size of 30-150 μm.
[0053] (2) 30 g of the powder obtained in step (1) was transferred to a high-pressure reactor with an effective volume of 200 ml, 150 ml of water was added for mixing, and then 6.0 g of hexadecyltrimethylammonium chloride (CTAC) was added. The reactor was reacted at 200° C. for 2 h and then naturally cooled.
[0054] (3) The product after the hydrothermal reaction was separated by centrifugation, washed three times with deionized water and ethanol, each time with 100 ml, and then calcined in a muffle furnace at 550° C. for 4 hours to obtain an oil-removing material.
[0055] Comparative Example 1
[0056] This comparative example provides an oil removal material, the preparation method of which is different from that of Example 1 only in that in step (1), 50 ml of 1 mol / L nitric acid is used to replace 50 ml of 1 mol / L hydrochloric acid.
[0057] Comparative Example 2
[0058] This comparative example provides an oil removal material, the preparation method of which is different from that of Example 1 only in that in step (2), an equal amount of dodecyltrimethylammonium bromide (DTAB) is used to replace hexadecyltrimethylammonium chloride (CTAC).
[0059] Comparative Example 3
[0060] This comparative example provides an oil removal material, the preparation method of which is different from that of Example 1 only in that in step (3), the material is calcined in a muffle furnace at 300° C. for 4 hours.
[0061] Test Example 1
[0062] The specific surface area (BET) and adsorption effect of the oil removal materials of Examples 1-3 and Comparative Examples 1-3 were tested.
[0063] The specific surface area was tested using a BET analyzer (Autosorb-iQ from Quantachrome).
[0064] Calculation formula:
[0065]
[0066] in:
[0067] S represents the specific surface area of the substance, in m 2 / g;
[0068] V m It represents the monolayer adsorption gas capacity, which indicates the amount of gas that can be adsorbed on the surface of a substance under specific conditions;
[0069] A m represents the cross-sectional area of nitrogen molecules in liquid hexagonal close packing at 77K, which is 16.2×10 -20 m 2 ;
[0070] NA stands for Avogadro's constant, which indicates the number of particles per mole of a substance, and its value is 6.022×10 23 .
[0071] Based on the multi-molecular layer adsorption theory, the BET analyzer can calculate the single-layer adsorption gas capacity V by measuring the amount of adsorbed gas at different pressures. m , and then use the above formula to calculate the specific surface area S.
[0072] The test conditions for the oil removal adsorption capacity (mg / g) are as follows: n-hexadecane dissolved in concentrated ammonia water is used as a simulated solution (oil content 100 mg / L, ammonia concentration 25%, pH 12) as the experimental medium, the oil removal material dosage is 1 g / L, and the adsorption reaction is carried out at room temperature (25°C) for 2 hours.
[0073] Calculate according to Q=V(C0-C) / m, where Q: adsorption amount (mg / g); V: reaction solution volume (L); C0: initial solution oil concentration (mg / L); C: solution oil concentration after reaction (mg / L); m: amount of oil removal material added (g).
[0074] The test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] The results show that the oil removal materials provided in Examples 1-3 of the present invention have more excellent specific surface area and oil removal adsorption capacity, indicating that in the preparation process of the composite material, hydrochloric acid is selected as a catalyst, CTAC is used as a template, and calcination is performed at a certain temperature, which can provide more effective oil removal active sites on the surface of the material, which is beneficial to improve the combination effect between the material surface and oil, thereby improving the surface oleophilicity of the material.
[0078] Test Example 2
[0079] The recovered ammonia water provided by a coal chemical enterprise was deoiled. The ammonia mass fraction of the water sample was 22%, pH 12.4, and the oil content was 55.2 mg / L.
[0080] The oil removal material of Example 1 was used to carry out an ammonia water oil removal test, and the steps were as follows: 10L of oil-containing ammonia water was pumped into the oil removal reaction tank, 20g of oil removal material was added, and the concentration of the oil removal material reached 2g / L. After mechanical stirring for 3h, a centrifuge was used for solid-liquid separation, the centrifugal speed was 1500 rpm / min, and the centrifugal time was 10min. The liquid obtained after centrifugation was the ammonia water after oil removal, the ammonia mass fraction was 22%, the oil content was reduced to 0.9 ppm, and the oil removal rate was 98.4%; the separated solid material entered the regeneration reaction tank, and 0.25L of ethanol (volume fraction 99%, temperature 25°C) was introduced and mixed and stirred for desorption, the desorption time was 1h, and solid-liquid separation was performed again, the adsorption material was regenerated, and it could enter the adsorption material storage tank for reuse. The regenerated liquid was recycled 3 times and then discharged as wastewater.
[0081] Test Example 3
[0082] The recovered ammonia water provided by a coal chemical enterprise was deoiled. The ammonia mass fraction of the water sample was 20%, pH 12, and the oil content was 104.8 mg / L.
[0083] The oil removal material of Example 2 was used to carry out an ammonia water oil removal test, and the steps were as follows: 10L of oil-containing ammonia water was pumped into the oil removal reaction tank, 40g of oil removal material was added, and the concentration of the oil removal material reached 4g / L. After mechanical stirring for 2h, a ceramic membrane (pore size 2μm) was used for solid-liquid separation. The separated water was ammonia water after oil removal, with an ammonia mass fraction of 20%, an oil content reduced to 1.5ppm, and an oil removal rate of 98.6%; the separated solid material entered the regeneration reaction tank, and 0.8L of sodium hydroxide solution (mass fraction 5%, temperature 70°C) was introduced and mixed and stirred for desorption. The desorption time was 1h, and solid-liquid separation was performed again. The adsorption material was regenerated and could enter the adsorption material storage tank for reuse. The alkali solution was recycled 3 times and then discharged as wastewater.
[0084] Test Example 4
[0085] The recovered ammonia water provided by a coal chemical enterprise was deoiled. The ammonia mass fraction of the water sample was 20.5%, pH 12.2, and the oil content was 170.5 mg / L.
[0086] The oil removal material of Example 3 was used to carry out an ammonia water oil removal test, and the steps were as follows: 20L of oil-containing ammonia water was pumped into the oil removal reaction tank, 160g of oil removal material was added, and the concentration of the oil removal material reached 8g / L. After mechanical stirring for 3h, a centrifuge was used for solid-liquid separation, the centrifugal speed was 1000 rpm / min, and the centrifugal time was 10min. The liquid obtained after centrifugation was the oil-free ammonia water, the ammonia mass fraction was 20.5%, the oil content was reduced to 1.8 ppm, and the oil removal rate was 98.9%; the separated solid material entered the regeneration reaction tank, and 2L of ethanol (volume fraction 99%, temperature 25°C) was introduced and mixed and stirred for desorption, the desorption time was 1h, and solid-liquid separation was performed again, the adsorption material was regenerated, and it could enter the adsorption material storage tank for reuse. The regenerated liquid was recycled 3 times and then discharged as wastewater.
[0087] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing an oil removal material, characterized in that: The method comprises the following steps: (1) tetraethyl orthosilicate, ferric acetate and magnesium acetate are subjected to hydrolysis and condensation reaction in the presence of a solvent and hydrochloric acid to form a transparent sol, and the sol is subjected to vacuum freeze-drying and grinding to obtain a powder; (2) the powder is subjected to a hydrothermal reaction with water and hexadecyltrimethylammonium chloride in a high-pressure reactor to obtain a hydrothermal product; (3) The hydrothermal product is centrifuged and washed, and then calcined at 500-600° C. to obtain the degreasing material.
2. The method for preparing the oil removal material according to claim 1, characterized in that: In step (1), The molar ratio of tetraethyl orthosilicate, ferrous acetate and magnesium acetate is 10:1-2:0.5-1; The solvent is ethanol, and the volume ratio of the solvent to tetraethyl orthosilicate is 20-100:1; The concentration of the hydrochloric acid is 0.5-3 mol / L, and the volume ratio of the hydrochloric acid to the solvent is 1:15-30; The temperature of the hydrolysis and condensation reaction is 10-50°C and the time is 1-3h; The vacuum freeze drying conditions are: temperature -30°C to -20°C, vacuum degree 5 to 10Pa, and time 12 to 24h; The particle size of the powder is 30-150 μm.
3. The method for preparing the oil removal material according to claim 1, characterized in that: In step (2), The solid-liquid ratio of the powder to water is 1-4:10, and the solid-liquid ratio of hexadecyltrimethylammonium chloride to water is 2-5:100; The temperature of the hydrothermal reaction is 180-220° C. and the time is 2-4 hours.
4. The method for preparing the oil removal material according to claim 1, characterized in that: In step (3), The solvents used for the washing are deionized water and ethanol; The calcination time is 2 to 5 hours.
5. A degreasing material, characterized in that: It is made by the method according to any one of claims 1-4.
6. Use of the oil removal material according to claim 5 in the oil removal process of ammonia water recovery in the coal chemical industry.
7. A deoiling method for recovering ammonia water in the coal chemical industry, characterized in that: The method comprises: The oil-containing ammonia water and the oil removal material as claimed in claim 5 enter the oil removal reaction unit for adsorption reaction to obtain a mixed liquid; The mixed liquid enters the solid-liquid separation unit for solid-liquid separation to obtain the oil-absorbed material and the oil-removed ammonia water; The oil-absorbed material enters the regeneration unit to undergo a desorption reaction with the regeneration liquid, and the resulting regenerated material returns to the oil removal reaction unit for reuse.
8. The deoiling method for recovering ammonia water in the coal chemical industry according to claim 7, characterized in that: The mass ratio of the oil content in the oil-containing ammonia water to the oil removal material is 1:10-50, and the hydraulic retention time of the oil removal reaction unit is 1-3 hours.
9. The deoiling method for recovering ammonia water in the coal chemical industry according to claim 7, characterized in that: The solid-liquid separation includes centrifugal separation or ceramic membrane filtration, wherein the rotation speed of the centrifugal separation is 1000-3000 rpm / min, and the pore size of the ceramic membrane is 0.5-5 μm.
10. The deoiling method for recovering ammonia water in the coal chemical industry according to claim 7, characterized in that: The solid-to-liquid ratio of the oil-absorbed material to the regenerated liquid is 1:5-20; The regeneration liquid is ethanol with a volume fraction of more than 98%, and the temperature of the desorption reaction is 20-40°C; or, the regeneration liquid is a sodium hydroxide aqueous solution with a mass fraction of 3%-5%, and the temperature of the desorption reaction is 60-80°C.
Citation Information
Patent Citations
A method for preparing a carboxylated iron tetroxide-polyamidine composite degreasing material
CN109364895B
System and method for treating wastewater containing complex organic pollutants and ammonia nitrogen
CN112047550A
Oil removal material for treating coking residual ammonia water as well as preparation method and use method of oil removal material
CN117244515A
Preparation method for mesoporous silicon oxide hollow microspheres with magnetic nanoparticles embedded in shell layers
CN102500296A
Preparation method of nanometer iron / meso-porous silicon composite material for treating heavy metal-polluted water
CN105344325A